2019
DOI: 10.1097/rct.0000000000000946
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion Data for Acute Ischemic Stroke Evaluation Using Rapid Software: Pitfalls of Automated Postprocessing

Abstract: Computed tomography perfusion (CTP) is increasingly used to determine treatment eligibility for acute ischemic stroke patients. Automated postprocessing of raw CTP data is routinely used, but it can fail. In reviewing 176 consecutive acute ischemic stroke patients, failures occurred in 20 patients (11%) during automated postprocessing by the RAPID software. Failures were caused by motion (n = 11, 73%), streak artifacts (n = 2, 13%), and poor contrast bolus arrival (n = 2, 13%). Stroke physicians should review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 8 publications
5
31
0
3
Order By: Relevance
“…The main reason for the higher failure rate of CTP might be that it was di cult for the patients to remain stationary during the longer scan time than CTA. In consistent with the prior study, we found that baseline NIHSS was the risk factor that signi cantly associated with CTP failure [9]. Patients with higher baseline NIHSS would be neurologically more severe, more restless, and more likely to be mobile during the scanning process.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The main reason for the higher failure rate of CTP might be that it was di cult for the patients to remain stationary during the longer scan time than CTA. In consistent with the prior study, we found that baseline NIHSS was the risk factor that signi cantly associated with CTP failure [9]. Patients with higher baseline NIHSS would be neurologically more severe, more restless, and more likely to be mobile during the scanning process.…”
Section: Discussionsupporting
confidence: 90%
“…Besides longer time consumption, CTP also showed higher failure rate than CTA in our study. Kauw et al reported a CTP failure rate of 11%, and they found that motion was the leading cause, followed by streak artifacts and poor contrast bolus arrival, which was in line with our study [9]. The main reason for the higher failure rate of CTP might be that it was di cult for the patients to remain stationary during the longer scan time than CTA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For these reasons, the multimodal evaluation of the whole neuroradiological examination (NCCT, all qualitative and quantitative CTP maps) must be underlined [46].…”
Section: Resultsmentioning
confidence: 99%
“…Eine Herausforderung für die Umsetzung der Studienergebnisse in die klinische Praxis stellt die automatisierte Bildverarbeitung dar. Die in EXTEND, DAWN und DEFUSE-3 verwendete RAPID-Software steht als kommerzielles Produkt nicht allen Krankenhäusern zur Verfügung und liefert in bis zu 11 % der Fälle fehlerhafte Segmentierungen von Infarktkern und Penumbra[30]. Die Auswertung nationaler und internationaler Schlaganfallregister wird Auskunft geben, in welchem Ausmaße von den strengen Studienkriterien in der Praxis abgewichen werden kann.…”
unclassified